Relationship of transcription factor 7 like 2 gene rs7903146 variation with type 2 diabetes and obesity related parameters - (:unkn) unknown (Elsevier Ltd, 2012)
Aims: The allele frequencies of transcription factor 7 like 2 (TCF7L2) gene rs7903146 polymorphism in type 2 diabetes mellitus (T2DM) and non-T2DM controls were determined. Methods: TCF7L2 rs7903146 genotypes were determined with qPCR. Results: The TCF7L2 gene rs7903146 genotype frequencies for homozygous wild type (C/C), heterozygous (C/T) and homozygous polymorphic (T/T) for T2DM patients were determined, respectively, as 71.4%, 14.3%, 14.3% and 72.5%, 11.8%, 15.7% for controls. The weight, length and lean body mass were higher in C/T + T/T compared to C/C carriers. Glucose, insulin, insulin resistance and homeostatic model assessment (HOMA) were nonsignificantly higher in rs7903146C/T + T/T in comparison to C/C. TCF7L2 gene rs7903146 genotypes were not found to interact with drugs. The absence of any difference between genotype frequencies among study groups indicates that no association persists with TCF7L2 gene rs7903146 polymorphism and T2DM. Conclusions: The effects of rs7903146 variation over some obesity variables suggest that this variation may effect T2DM development via obesity. © 2012 Diabetes India.
Keywords: Fat mass; Insulin resistance; Obesity; rs7903146 polymorphism; Serum lipids; TCF7L2